IberSPEECH 2021 2021
DOI: 10.21437/iberspeech.2021-55
|View full text |Cite
|
Sign up to set email alerts
|

Active correction for speaker diarization with human in the loop

Abstract: State of the art diarization systems now achieve decent performance but those performances are often not good enough to deploy them without any human supervision. In this paper we propose a framework that solicits a human in the loop to correct the clustering by answering simple questions. After defining the nature of the questions, we propose an algorithm to list those questions and two stopping criteria that are necessary to limit the work load on the human in the loop. Experiments performed on the ALLIES da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Max/Min selects the couple of segments, one from each branch, with the lowest (max) or highest (min) similarity in terms of PLDA score (distance). The results of our study [10] showed that Max/Min criterion are not competitive and we thus only focus on Longest and Cluster center in this work.…”
Section: Within-show Question Generation Modulementioning
confidence: 96%
See 3 more Smart Citations
“…Max/Min selects the couple of segments, one from each branch, with the lowest (max) or highest (min) similarity in terms of PLDA score (distance). The results of our study [10] showed that Max/Min criterion are not competitive and we thus only focus on Longest and Cluster center in this work.…”
Section: Within-show Question Generation Modulementioning
confidence: 96%
“…Final performance assessment of a human assisted system must take into account the cost of human interaction in order to evaluate the quality of the interaction process. Penalized DER (DER pen ), a metric introduced in [10], is used to merge the information about the final performance (after human interaction) with the cost of the interaction required to reach this result. This metric adds a constant amount of error time, called penalized time (t pen ), to the diarization error time, for each question asked to the human expert.…”
Section: Human Interaction Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Constraints can be combined with several clustering algorithms, such as k-means [20] or HAC [21]. In this work we use a constrained spectral clustering approach, where constraints are integrated via the exhaustive and efficient constraint propagation (E 2 CP) algorithm [22], which was recently applied in diarization settings [19].…”
Section: Constrained Spectral Clusteringmentioning
confidence: 99%